Inflammatory diseases of the pelvic organs: pathogenetic aspects, diagnosis, clinic, treatment (review) - N A Buralkina; A S Katkova; E E Arutyunova; V E Zhorova; Z K Batyrova; G A Vlasova (Гинекология, 2018)
The article deals with modern concepts of pathogenetic mechanisms of inflammatory diseases of the pelvic organs, as well as approaches to diagnosis and treatment from the perspective of the possibility of using Nimesil as part of complex therapy.